(3QSGdI aj Cf GdSYGOI Jchf aj GdBNQIs
(3ChdgG (B:s
(3dh WQb ddYGbd Zdi UQa GdeYQha Yf GdeYGQa NUhUkG EPG cGf GdeYQha CaVd YUeI jJeSc HgG cd ef SYO HGdMjGI s
(3BNQgG (B:s
(3hBNQ GdehLhO efgG (B: (3hPdc Ydi bSejf EeG Cf jche dcd ai hGMO efgG Ch dHYVgG JeGe s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdKGfis
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
(3JHUQGJ GdCUd (B:s
(3GdfSNI eHJhQI GdBNQ s
(3eUOQ GbJfGA GdCUd (B:s
(3eLdS ThQGi (B(599) s
Keywords: (3GdadSaI hGdefWbs